Pengaruh Media Sosial terhadap Pemahaman Isu Sosial pada Siswa dalam Pembelajaran IPS di Sekolah SMP IT Ibnu Halim: Penelitian - Christella Miranda Josephine Simbolon; Khairiah; Primawati Sinaga; Rani Selfia Sipayung; Andi Taufiq Umar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the effect of social media use on social issue comprehension among students at SMP IT Ibnu Halim. The research uses a quantitative approach with an associative research design, examining the relationship between the independent variable (social media) and the dependent variable (social issue comprehension). The sample consists of 30 students selected using purposive sampling. Data were collected through a Likert scale-based questionnaire that was tested for validity and reliability. Data analysis was performed using descriptive and inferential statistics, specifically simple linear regression, to determine the impact of social media on social issue comprehension. Prior to analysis, classical assumption tests were conducted to ensure that the data met the criteria for regression analysis. The results show that social media use has a significant effect on students' comprehension of social issues, with a very low significance value of 0.000. These findings have important implications for the development of technology-based learning in schools.